Preferences for Sin Taxes - Tobias König; Renke Schmacker (Center for Economic Studies and ifo Institute (CESifo), 2022)
Sin taxes have become a widely suggested policy instrument to discourage the consumption of goods deemed harmful to individuals and society. Using surveys and experiments on a representative sample of the US population, we provide evidence on how individuals think and reason about such corrective policies. We reveal that preferences for taxes on sugar-sweetened beverages (SSBs) are driven by normative considerations, including efficiency-related ideas and distributional concerns. In contrast, self-interested motives play only a minor role. Among the efficiency arguments, people place relatively large weight on externality correction, and motives to correct health cost misperceptions matter more than motives to correct a lack of self-control. However, anti-paternalistic attitudes and regressivity concerns are also prevalent, which helps to explain why the majority of respondents oppose SSB taxes, even though they agree that behavioral biases and externalities are relevant. Preferences for SSB taxes turn out to be malleable. Explaining to individuals the idea behind corrective taxation yields significant increases in the support for SSB taxes and the general openness to paternalistic intervention.
Keywords: H23; I18; D12; D78; 330; sin tax; internality; externality; soda tax; self-control